Perspectives of breastfeeding of the infant with cleft lip and/or palate: an integrative literature review (Research, Society and Development, 2023)
Objective: identifying strategies for breastfeeding infants with cleft lip and/or palate. Methodology: This is an Integrative Literature Review (RIL), using the databases of the Virtual Health Library, LILACS, MEDLINE and BDENF. The search was carried out in January 2023. Using the PICO strategy, the research question was formulated: What leads to successful breastfeeding in infants with cleft lip and/or palate? For the search, Health Sciences Descriptors (DeCS) were used with the operators “AND” and “OR” associating the descriptors exhaustively. Results: five studies were identified, mostly Brazilian (three studies), one in Uganda and the other in Chile. Factors related to the level of evolution of the condition of the infant's lip and/or palate play an important role in the success or difficulties of breastfeeding. The stigma related to the pathological condition is also a discouraging factor for the continuity of breastfeeding. Guidance and support by the care team is described as a moderating factor for the success of the practice. Conclusion: with the challenges of breastfeeding in relation to the mother-baby binomial, the greater the complexity of the fissure, the lower the chance of the child receiving exclusive breastfeeding, if there is no adequate support.